Marine communal property right or marine traditional right are marine property right is owned by communal and It is an important aspect for managing marine resources.. This study is aimed to describe and analyzes the components of institution of marine communal property right Result of this study is able to arrange management of marine reusources based on traditional property right by considering performances of economics, social and environmental. The institution of marine traditional right at - Gatot Yulianto (Buletin Ekonomi Perikanan, 2008)
Marine communal property right or marine traditional right are marine property right is owned by communal and It is an important aspect for managing marine resources.. This study is aimed to describe and analyzes the components of institution of marine communal property right Result of this study is able to arrange management of marine reusources based on traditional property right by considering performances of economics, social and environmental. The institution of marine traditional right at coastal villages In Bintuni Bay is an organization system and is as a system of control to marine resources that are reffered.by (1) Jurisdiction of boundary that referring a region and a scope of owned authority by local communal and In this cases are established by (a) sense of community based on a familiar relationships and social relationships (b) homogenity; to exploiting marine resources for fullfill their needs together; (2) Property Right that is sourced from traditional laws based on legacy and from concensus among of members of community or other convnunlty. This communal prperty right In this. case is contain of social and economic aspect; (3) Role of representative that referring members of community to take a decision process to manage marine resources.